More than 1,500 attend RTM's Malaysia Aspiration Tour and UMPSA's Independence Day Celebration - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 31 August 2024 – More than 1,500 people attended the RTM Malaysia Aspiration Tour and the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Independence Night Celebration recently at the UMPSA Mini Stadium, Gambang Campus.